Modelo preditor do espessamento da carótida em adolescentes com excesso de peso baseado em indicadores cardiometabólicos - Medeiros, Camila Muniz (2023)
INTRODUCTION: Prevention and care for adolescents with obesity pose a challenge for public health services due to the complexity of their approach, particularly in primary health care, which serves as the gateway to the health care network (RAS) of the Unified Health System (SUS). Childhood obesity, along with associated chronic diseases such as type 2 diabetes and hypertension, predispose individuals to the development of subclinical atherosclerotic disease (SAD) and subsequent cardiovascular events such as acute myocardial infarction and stroke. The influence of cardiometabolic risk factors on SAD depends on the phase of atherogenesis and the nutritional status of the individual. Knowledge about predictors of SAD in overweight adolescents is crucial for developing more effective actions in Primary Health Care and guiding the flow within the RAS. Few studies have assessed the role of these factors in overweight adolescents. OBJECTIVE: To investigate cardiometabolic markers that predict Carotid Intima-Media Thickness (CIM) in overweight adolescents (overweight or obese). METHODS: This cross-sectional study involved 161 overweight adolescents from public high schools. Data from two previous studies, "Subclinical Atherosclerotic Disease in Adolescents: Relationship with Pathobiological Determinants of Atherosclerosis in Youth, High-Sensitivity C-Reactive Protein, and Pulmonary Function" and "Impact of Active Video Game Use within a Gamification Protocol on Cardiorespiratory Risk in Overweight or Obese School Adolescents: A Randomized Intervention Study," conducted by researchers from the Center for Epidemiological Studies, Extension, and Research (NEEPE) linked to the graduate program in public health at UEPB, were used for this research. The study included overweight adolescents who had undergone carotid ultrasonography. The analyzed variables were age, sex, CIM thickness, blood pressure, nutritional status, central adiposity, lipid profile, and glycemic profile. The data were consolidated into a single database for analysis in the current study. Descriptive analysis (measures of central tendency and dispersion, as well as absolute and relative frequencies) was performed for all variables. The distribution of variables was assessed using the Kolmogorov-Smirnov test. The correlation between the dependent variable (CIM thickness) and independent variables (age, sex, blood pressure, nutritional status, central adiposity, lipid profile, and glycemic profile) was evaluated using the Pearson or Spearman correlation test. To analyze predictors of CIM thickness, a multiple regression model with a Gamma distribution, belonging to the Generalized Linear Models (GLM) class, was constructed, including variables with a p ≤ 0.20. Statistical analysis was performed using SPSS version 22 and R software version 4.3.0, with a significance level of 5% for all statistical tests. RESULTS: The median age of the evaluated adolescents was 15.0 (13.1-16.0), and 26.7% were obese. Elevated CIM thickness was present in 23.7% of the study sample, with low HDL cholesterol (62.7%) being the most frequent cardiometabolic risk factor and elevated fasting blood glucose (5.6%) being the least frequent. A positive correlation was observed between carotid CIM thickness and fasting blood glucose (r=0.17; p=0.032) and a negative correlation with age (r= -0.17; p=0.027). Fasting blood glucose and age were identified as predictors of CIM thickness in the evaluated adolescents, with a 1% increase in the average CIM thickness for every year younger and approximately a 0.24% increase for every mg/dL increase in fasting blood glucose. CONCLUSION: The prevalence of high carotid thickness in overweight adolescents was significant, with fasting blood glucose and age being predictors of CIM thickness, with a greater impact in younger individuals. The data from this study showed that higher fasting blood glucose in younger adolescents increases the likelihood of elevated CIM thickness.